2003
DOI: 10.1074/jbc.m208623200
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the V1 ATPase from Manduca sexta into Subcomplexes and Visualization of an ATPase-active A3B3EG Complex by Electron Microscopy

Abstract: The effect of the ATPase activity of Manduca sexta V 1 ATPase by the amphipathic detergent lauryldimethylamine oxide (LDAO) and the relationship of these activities to the subunit composition of V 1 were studied. The Vacuolar ATPases (V 1 V O ATPases) define an ubiquitous class of proton pumps, which utilize ATP hydrolysis to maintain an acidic pH inside the vacuole (1). The electrochemical ion gradient created across the vacuolar membrane is used for the accumulation of positively charged substrates such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Therefore, this density can indicate the presence of subunit G. Such close proximity of subunit G to E has been described from binding (24) and zero-length cross-link experiments (50). In line with these findings are the most recent data of the V 1 -ATPase from M. sexta demonstrating that the "core" complex consists at least of the four subunits A, B, E, and G and that it still retains 58% of hydrolytic ATPase activity (26). Averaged projections of this core complex show a hexagonal arrangement of the major subunits A and B surrounding a seventh mass composed of both subunits E and G. Furthermore, subunit G of the yeast vacuolar ATPase exists in solution as an elongated dimer (8.0 Ϯ 0.3 nm) (33).…”
Section: Structure Of a F 1 -/V 1 -Atpase Hybrid Complexsupporting
confidence: 75%
“…Therefore, this density can indicate the presence of subunit G. Such close proximity of subunit G to E has been described from binding (24) and zero-length cross-link experiments (50). In line with these findings are the most recent data of the V 1 -ATPase from M. sexta demonstrating that the "core" complex consists at least of the four subunits A, B, E, and G and that it still retains 58% of hydrolytic ATPase activity (26). Averaged projections of this core complex show a hexagonal arrangement of the major subunits A and B surrounding a seventh mass composed of both subunits E and G. Furthermore, subunit G of the yeast vacuolar ATPase exists in solution as an elongated dimer (8.0 Ϯ 0.3 nm) (33).…”
Section: Structure Of a F 1 -/V 1 -Atpase Hybrid Complexsupporting
confidence: 75%
“…Previous data from photoactivated cross-linking of unique cysteine residues on subunit B suggested that subunits E and G are part of the peripheral stalk connecting the V 1 and V 0 domains and that subunit D is located in the interior of the A 3 B 3 hexameric head, thus making it the likely homolog to the ␥ subunit in F 1 (14,15). The peripheral location of subunit E has been challenged by electron microscopy data obtained on the V 1 domain of the Manduca sexta V-ATPase (50). One question in attempting to reconcile these two sets of data is the accuracy of the structural model of the V 1 domain on which the interpretation of the cross-linking data is based.…”
Section: Position Of Subunit H In the Yeastmentioning
confidence: 98%
“…The gross structure and tentative subunit positions in the complex have emerged through cross-linking studies (Graham et al 2000;Gru¨ber et al 2001) complemented by lowresolution structural information from electron microscopy (Boekema et al 1997(Boekema et al , 1999Wilkens et al 1999;Ubbink-Kok et al 2000;Domgall et al 2002). Electron microscopy has confirmed that the isolated V 1 domain is a hetero hexametric complex of alternating A and B subunits (Radermacher et al 1999(Radermacher et al , 2001Gru¨ber et al 2000;Rizzo et al 2003). The asymmetric protein ring, as well as the 7-fold symmetry of the c ring, has been visualized by electron microscopy, demonstrating that the V o domain is the rotor responsible for proton translocation (Wilkens and Forgac 2001;Murata et al 2003).…”
Section: Introductionmentioning
confidence: 93%